If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23x + 9 = 101 Reorder the terms: 9 + 23x = 101 Solving 9 + 23x = 101 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 23x = 101 + -9 Combine like terms: 9 + -9 = 0 0 + 23x = 101 + -9 23x = 101 + -9 Combine like terms: 101 + -9 = 92 23x = 92 Divide each side by '23'. x = 4 Simplifying x = 4
| 5(2-3)=3(3x+2) | | 3x-x^3=0 | | 2x+11=3x | | x+5=x+7-2 | | 3x-1=-x-1 | | 9x-3=-2x+19 | | 39=.5(17x+6-7x-2) | | 5*0+0+11*-0.09090909091+-0.5454545455*0*-1=1 | | (5x+x+(11*(-0.09090909091+-0.5454545455x)))*-1=1 | | (5x+x+(11*-0.09090909091+-0.5454545455x))*-1=1 | | -2b+3b=-1 | | (5x+x+11t)*-1=1 | | (5x)+x+11t*-1=1 | | (5x^2)-5x^2=0 | | 25x+24y=11.1 | | (5x^2)+5i=0 | | 4.0x=13.2 | | 98x*4t=5 | | 3x-1=7x+1 | | 8.8x=30.8 | | 10=-z+3 | | 8x^2-8x+77=0 | | k*2.7=21 | | h*0.3=19 | | 8m=2(j+4+3m) | | 49.6+5*x=(10+x)5.4 | | x^5+4x^3-2x^2-8=0 | | 49.6+5*x=5.4(10+x) | | 49.6+10*x=5.4(10+x) | | y=4x^3-7x-3x^2+6 | | 28.8+x*6=(6+x)(5.4) | | 24.78+x*6=(6+x)(5.4) |